2015
DOI: 10.1255/ejms.1366
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Chondroitin Sulfate Glycosaminoglycans Using Collision-Induced Dissociation; Uronic Acid Cross-Ring Diagnostic Fragments in a Single Stage of Tandem Mass Spectrometry

Abstract: The stereochemistry of the hexuronic acid residues of the structure of glycosaminoglycans (GAGs) is a key feature that affects their interactions with proteins and other biological functions. Electron based tandem mass spectrometry methods, in particular electron detachment dissociation (EDD), have been able to distinguish glucuronic (GlcA) from iduronic acid (IdoA) residues in some heparan sulfate tetrasaccharides by producing epimer-specific fragments. Similarly, the relative abundance of glycosidic fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Different studies have reported the comprehensive MS characterization of the various sulfated dp2 isomers from glucosaminoglycans allowing decisive progresses in the compositional analysis and profiling of heparin and heparan sulfate from multiple origins . Less data are comparatively available for galactosaminoglycan‐derived oligosaccharides, especially as regards the detailed characterization of chondroitin sulfate oligosaccharides . Previous studies showed that MS/MS fragmentation of CS‐A and CS‐C dp2 produced identical Y 1 and Z 1 fragments with different respective intensities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have reported the comprehensive MS characterization of the various sulfated dp2 isomers from glucosaminoglycans allowing decisive progresses in the compositional analysis and profiling of heparin and heparan sulfate from multiple origins . Less data are comparatively available for galactosaminoglycan‐derived oligosaccharides, especially as regards the detailed characterization of chondroitin sulfate oligosaccharides . Previous studies showed that MS/MS fragmentation of CS‐A and CS‐C dp2 produced identical Y 1 and Z 1 fragments with different respective intensities .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Less data are comparatively available for galactosaminoglycan-derived oligosaccharides, especially as regards the detailed characterization of chondroitin sulfate oligosaccharides. [25][26][27][28][29][30] Previous studies showed that MS/MS fragmentation of CS-A and CS-C dp2 produced identical Y 1 and Z 1 fragments with different respective intensities. 31,32 Therefore, the determination of the 4S/6S sequence of CS could not rely unambiguously on these fragment ions only, but must also involve the measurement of their intensity or further multistage (MS n ) collision-induced dissociation.…”
mentioning
confidence: 99%
“…In the last decade, ESI MS contributed a significant progress to compositional and structural analysis of glycosaminoglycans (GAGs) with a particular emphasis on the determination by advanced MS/MS techniques of chain sequences, the complex sulfation patterns, and their correlation with certain biological activities . However, ESI MS has encountered a number of impediments, the most severe being the difficulty to ionize long GAG chains, prevent the in‐source fragmentation of the labile sulfate groups, generate multiply charged ions of high molecular weight (MW) species, simultaneously ionize and detect chains of variable sulfation degree, and distinguish the isobaric structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous EDD and CID reports have shown the presence of sodium counter ions can provide a means to control stereochemical dependent fragmentation [21, 36]. We found that to be very useful for the tri and tetra-sulfated HS standards.…”
Section: Resultsmentioning
confidence: 80%
“…[35]. The ability to assign the C-5 stereochemistry in uronic acid residues of 4- O -sulfo chondroitin sulfate epimers with varying oligomer lengths (dp4–dp10) based on diagnostic cross-ring ions 2,4 A n , and 0,2 X n in CID mass spectra has also been reported by Kailemia et al [36]. Compared to heparan sulfates, chondroitin sulfates have well-defined sulfation pattern, hence the former requires a more sensitive activation method for stereochemistry assignments.…”
Section: Introductionmentioning
confidence: 82%